Penerapan Prinsip Etika Bisnis Islam di Lazizaa Chicken & Pizza Kedungturi Sidoarjo - Prameswary, Titan Nia; Suryaningsih, Sri Abidah (Jurnal Ekonomika dan Bisnis Islam, 2020)
Abstract :This research is focused on discussing the application of Islamic business ethics used by restaurant restaurants in Sidoarjo namely Lazizaa Chicken & Pizza Kedungturi Sidoarjo. In Islam, an economic activity carried out by a Muslim must have mutual benefit elements or values. The application that is carried out is also applied in every aspect of the economy consisting of the organization of production, consumption and distribution. Researchers use the basic values of Islamic business ethics as a reference to measure the application of Islamic business ethics including Unity, Balance, Free Will, Responsibility, and Truth: Virtue and Honesty. Through a qualitative approach, there are two issues that must be answered namely how the application of Islamic business ethics in Lazizaa Chicken & Pizza Kedungturi Sidoarjo is carried out and how Islamic business ethics principles are carried out in their success in doing business. Like praying 5 times, Lazizaa Chicken & Pizza is still running buying and selling activities and serving buyers. So that researchers can collect three components, namely data reduction, data presentation, and data verification. The results of the study indicate that Lazizaa Chicken & Pizza Kedungturi Sidoarjo applies Islamic business ethics in doing business but on the principle of unity Lazizaa Chicken & Pizza, has not been fully expected. For example, when the Adhan reverberated employees and employees were still making buying and selling transactions and serving consumers. The principles of Islamic business ethics used include the principle of balance, the principle of free will, the principle of responsibility and the principle of truth: virtue and honesty.